2022
DOI: 10.3389/fphys.2021.800301
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Microarchitecture Improvement Is Associated With Skeletal Nerve Increase Following Aerobic Exercise Training in Middle-Aged Mice

Abstract: Advancing age is associated with bone loss and an increased risk of osteoporosis. Exercise training improves bone metabolism and peripheral nerve regeneration, and may play a critical role in osteogenesis and increase in skeletal nerve fiber density. In this study, the potential positive role of aerobic exercise training in bone metabolism and skeletal nerve regeneration was comprehensively evaluated in 14-month-old male C57BL/6 mice. The mice were divided into two groups: no exercise (non-exercise group) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Given sclerostin is a potent inhibitor of bone formation, ( 37 ) we next examined whole‐body bone mineral properties and tibial microarchitecture, a bone region known to demonstrate exercise‐induced responses as a result of increased mechanical loading. ( 38 ) Whole‐body in vivo change in BMC was not influenced by exercise training (F = 2.6, p = 0.1) or sclerostin treatment (F = 0.3, p = 0.6) and there was no exercise*sclerostin interaction (F = 0.4, p = 0.6) (Fig. 4 A ).…”
Section: Resultsmentioning
confidence: 91%
“…Given sclerostin is a potent inhibitor of bone formation, ( 37 ) we next examined whole‐body bone mineral properties and tibial microarchitecture, a bone region known to demonstrate exercise‐induced responses as a result of increased mechanical loading. ( 38 ) Whole‐body in vivo change in BMC was not influenced by exercise training (F = 2.6, p = 0.1) or sclerostin treatment (F = 0.3, p = 0.6) and there was no exercise*sclerostin interaction (F = 0.4, p = 0.6) (Fig. 4 A ).…”
Section: Resultsmentioning
confidence: 91%
“…Given sclerostin is a potent inhibitor of bone formation [30], we next examined whole body bone mineral properties and tibial microarchitecture, a bone region known to demonstrate exercise induced responses as a result of increased mechanical loading (e.g., [31]). Whole body in vivo change in BMC was not influenced by exercise training (p = 0.1) or sclerostin injection (p = 0.6) and there was no exercise*injection interaction (p = 0.6) (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Few research has been done so far on the impact of circRNAs on bone during exercise, however, to understand their purpose, further research is needed to elaborate on their effects. Lee et al (85) found that improvements in trabecular bone microarchitecture in middle-aged mice were directly associated with increased skeletal nerves after aerobic exercise training. And the expression of seven upstream osteogeneses and neuroplasticity non-coding RNAs, including miR-491-3p, miR-470-5p, let-7a-5p, miR-137-3p, miR-130a3p, and miR-29b-3p, were upregulated after 8 weeks of treadmill activity training.…”
Section: The Role Of Exercise In Autophagymentioning
confidence: 99%